Causes and Associated Factors of Headaches among 5 to 15-year-old Children Referred to a Neurology Clinic in Kashan, Iran - TALEBIAN, Ahmad; SOLTANI*, Babak; HAJI REZAEI, Mostafa (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Talebian A, Soltani B, Haji Rezaei M. Causes and Associated Factors of Headaches among 5 to 15-year-old Children Referred to a Neurology Clinic in Kashan, Iran. Iran J Child Neurol. 2015 Winter;9(1):71-75. Abstract Objective Headaches are common neurologic problems for children and adolescents. They are divided into two types: primary and secondary. Primary headaches include migraines and tension-type as well as comprise the majority of headaches. We detect the causes of headaches and their associations with demographic variables among children and adolescents. Materials & Methods This cross-sectional study was performed on 5–15 year-old children with headaches from March 2010 to April 2012 who presented at a pediatric neurology clinic in Kashan, Iran. Diagnosis of headaches was done in accordance with the International Classification of Headache Disorders. Data regarding the type of headache, age, gender, pain severity, aura, family history, and sleep disorder were collected. Results One hundred fourteen children (44 male and 70 female) with headaches were enrolled in the study. The types of headaches were comprised as follows: 67 cases of migraines, 38 cases of tension-type headaches, 2 cases of cluster headaches, and 7 cases of secondary headaches. Pulsating headaches, family history of headaches, insomnia, and pain severity had higher prevalence in migrainous patients. Conclusion Physicians should extend their information gathering about primary and secondary headaches. Sleep disturbances and a family history of headaches were the most important factors associated with migraine headaches. References Cuvellier JC, Donnet A, Guegan-Massardier E, Nachit-Ouinekh F, Parain D, Vallee L. Treatment of primary headache in children: a multicenter hospital-based study in France. J Headache Pain 2009; 10: 447-53. Lateef TM, Merikangas KR, He J, Kalaydjian A, Khoromi S, Knight E, et al. Headache in a national sample of American children: prevalence and comorbidity. J Child Neurol 2009; 24: 536-43. Zwart JA, Dyb G, Holmen TL, Stovner LJ, Sand T. The prevalence of migraine and tension-type headaches among adolescents in Norway. The Nord-Trondelag Health Study (Head-HUNT-Youth), a large populationbased epidemiological study. Cephalalgia 2004; 24: 373- 9. Isik U, Topuzoglu A, Ay P, Ersu RH, Arman AR, Onsuz MF, et al. The prevalence of headache and its association with socioeconomic status among schoolchildren in istanbul, Turkey. Headache 2009; 49: 697-703. Abu-Arafeh I, Macleod S. Serious neurological disorders in children with chronic headache. Arch Dis Child 2005; 90: 937-40. Lewis DW. Headaches in children and adolescents. Am Fam Physician 2002; 65: 625-32. The International Classification of Headache Disorders: 2nd edition. Cephalalgia 2004; 24 Suppl 1: 9-160. Tavasoli A, Aghamohammadpoor M, Taghibeigi M. Migraine and Tension-Type Headache in Children and Adolescents Presenting to Neurology Clinics. Iran J Pediatr 2013; 23: 536-540. Bruni O, Fabrizi P, Ottaviano S, Cortesi F, Giannotti F, Guidetti V. Prevalence of sleep disorders in childhood and adolescence with headache: a case-control study. Cephalalgia 1997; 17: 492-8. Isik U, Ersu RH, Ay P, Save D, Arman AR, Karakoc F, et al. Prevalence of headache and its association with sleep disorders in children. Pediatr Neurol 2007; 36: 146-51. Miller VA, Palermo TM, Powers SW, Scher MS, Hershey AD. Migraine headaches and sleep disturbances in children. Headache 2003; 43: 362-8. Lewis DW, Ashwal S, Dahl G, Dorbad D, Hirtz D, Prensky A, et al. Practice parameter: evaluation of children and adolescents with recurrent headaches: report of the Quality Standards Subcommittee of the American Academy of Neurology and the Practice Committee of the Child Neurology Society. Neurology 2002; 59: 490-8. Lewis DW,Koch T. Headache evaluation in children and adolescents: when to worry? When to scan? Pediatr Ann 2010; 39: 399-406. Hershey AD, Powers SW, Bentti AL, Degrauw TJ. Effectiveness of amitriptyline in the prophylactic management of childhood headaches. Headache 2000; 40: 539-49. Donald W. Headache in children and adolescent. Am Fam Physician 2002; 65: 625-33. Kroner-Herwig B, Gassmann J. Headache disorders in children and adolescents: their association with psychological, behavioral, and socio-environmental factors. Headache 2012; 52: 1387-401. Wober-Bingol C, Wober C, Wagner-Ennsgraber C, Zebenholzer K, Vesely C, Geldner J, et al. IHS criteria and gender: a study on migraine and tension-type headache in children and adolescents. Cephalalgia 1996; 16: 107-12. Abu-Arafeh I,Russel G. Prevalence of headache and migraine in schoolchildren. British medical journal 1994; 308: 765-9. Ayatollahi SM,Khosravi A. Prevalence of migraine and tension-type headache in primary-school children in Shiraz. East Mediterr Health J 2006; 12: 809-17. Fallahzadeh H,Alihaydari M. Prevalence of migraine and tension-type headache among school children in Yazd,Iran. J Pediatr Neurosci 2011; 6: 106-9. Russell MB, Iselius L, Ostergaard S, Olesen J. Inheritance of chronic tension-type headache investigated by complex segregation analysis. Hum Genet 1998; 102: 138-40. Stewart WF, Linet MS, Celentano DD, Van Natta M, Ziegler D. Age and sex specific incidence rates of migraine with and without visual aura. Am J Epidemiol 1991; 134: 1111-20. <!--[if gte mso 9]> <![endif]-->